Diagnosis of inhomogeneous one-dimensional discrete chains by photon scattering - Gerasymov, Oleg I.; Sidletska, Liudmyla M. (Kyiv National University of Construction and Architecture, 2022)
Among the ways to reduce radiation doses (increasing the distance from the source to the person, reducing the time spent in radiation fields, reducing the radiation dose rate of the source) an important role is played by shielding the source of ionizing radiation.Currently, the use of screens is limited by the small selection of materials and the inconvenience of their use, which complicates their operation, installation and replacement, or disassembly.The propagation of a plane wave in a one-dimensional force chain with Hertzian contacts is analyzed in a linear approximation for cases with the presence of incorporated single and double impurities (defects). The algorithm of analytical solution of control equations and finding of reflection and transmission coefficients of incident radiation is determined. In terms of phase shifts, the frequency criterion of multi-modes of generation of transparent modes for inhomogeneous chains (with double impurities) similar to the Ramsauer-Townsend effect in the scattering of electrons by inert gas atoms is established. The obtained theoretical results are consistent with the data obtained from alternative sources. Possibilities of application of terahertz spectroscopy of radiation transmission for structural diagnostics and detection of in homogeneities, impurities and defects in discrete micro-mechanical (granular) systems are discussed. In particular, preliminary experimental data on scattering of terahertz radiation on samples of granular materials with different degrees of packing, from low to densely packed, which clearly indicate the dependence of the transmittance on the degree of packing and the formation of the corresponding band structure of spectra. The obtained results are also discussed in terms of applications to the creation of the element base of photonic circuitry in the sub millimeter range using decorated with impurities and structured low-dimensional discrete power circuits.